Body mass index (BMI) but not body weight is associated with changes in the metabolism of risperidone; A pharmacokinetics-based hypothesis. (November 2016) - Paulzen, Michael; Haen, Ekkehard; Stegmann, Benedikt; Hiemke, Christoph; Gründer, Gerhard; Lammertz, Sarah E.; Schoretsanitis, Georgios
Highlights: Body weight was shown to be a pharmacokinetic irrelevant parameter for risperidone. BMI correlated positively with active metabolite and active moiety of risperidone. Significant pharmacokinetic changes were detected in obese and cachectic patients. Abstract: Objective: We sought to unravel the influence of body weight and body mass index (BMI), both consistently reported as pharmacokinetic relevant parameters, on metabolism of risperidone in a naturalistic sample. Methods: Conducting non parametrical tests we sought for correlations between plasma concentrations of RIS, 9-OH-RIS and AM and body weight and BMI in patients out of a therapeutic drug monitoring (TDM) database. Further, we stratified patients to three groups based upon BMI values and compared drug concentrations between groups. Results: Although body weight failed to correlate with pharmacokinetic parameters, BMI was positively correlated with plasma concentrations of the active metabolite (9-OH-RIS) (rs = 0.121, p = 0.002) and active moiety (sum of RIS + 9-OH-RIS) (rs = 0.128, p = 0.001) as well as dose adjusted plasma concentrations of the active moiety (rs = 0.08, p = 0.04). The comparison of pharmacokinetic parameters between different BMI groups yielded lower plasma concentrations of 9-OH-RIS in patients with low BMI (<20 kg/m 2 ) and higher plasma concentrations of the active moiety in obese patients (BMI ≥30 kg/m 2 ) when compared with the control group (30 > BMI ≥ 20 kg/m 2 ). By comparing low vs. high BMI patients, the latter group showed higher 9-OH-RIS plasma concentrations. Conclusions and limitations: Considerable alterations in metabolism of risperidone were detected when comparing obese and cachectic patients with the control group in alignment with the positive correlation between BMI values and plasma concentrations of the active metabolite and active moiety as well as dose adjusted plasma concentrations of the active moiety. We suggest changes in CYP2D6 or CYP3A4 activity or differences in P -glycoprotein function in obese patients with greater BMI as a plausible mechanism underlying these alterations.